2011
DOI: 10.1021/jf1032729
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Proanthocyanidin Dimers and Trimers, Flavone C-Glycosides, and Antioxidants in Ficus deltoidea, a Malaysian Herbal Tea

Abstract: Phenolic compounds in an aqueous infusion of leaves of Ficus deltoidea (Moraceae), a well-known herbal tea in Malaysia, were analyzed by HPLC coupled to photodiode array and fluorescence detectors and an electrospray ionization tandem mass spectrometer. Following chromatography of extracts on a reversed phase C(12) column, 25 flavonoids were characterized and/or tentatively identified with the main constituents being flavan-3-ol monomers, proanthocyanidins, and C-linked flavone glycosides. The proanthocyanidin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
70
1
3

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 105 publications
(77 citation statements)
references
References 44 publications
3
70
1
3
Order By: Relevance
“…Ong et al (2011) demonstrated enhancement of flavonoid compounds (rutin, quercetin, and naringenin) in cell cultures of F. deltoidea influenced by different carbon sources as well as plant growth regulators [25]. A comprehensive study on flavonoid compounds of aqueous extract of F. deltoidea was conducted by Omar et al (2011) using HPLC-MS-based methodology and more than 25 compounds were identified [24]. Currently, two bioactive constituents known as vitexin and isovitexin have been isolated, identified, and evaluated to show α-glucosidase inhibition [6].…”
Section: Resultsmentioning
confidence: 99%
“…Ong et al (2011) demonstrated enhancement of flavonoid compounds (rutin, quercetin, and naringenin) in cell cultures of F. deltoidea influenced by different carbon sources as well as plant growth regulators [25]. A comprehensive study on flavonoid compounds of aqueous extract of F. deltoidea was conducted by Omar et al (2011) using HPLC-MS-based methodology and more than 25 compounds were identified [24]. Currently, two bioactive constituents known as vitexin and isovitexin have been isolated, identified, and evaluated to show α-glucosidase inhibition [6].…”
Section: Resultsmentioning
confidence: 99%
“…Flavonoid has been reported for several Ficus species [12,14,22,23]. Indication for the presence of several flavonoids in leaves samples comes from the molecular ion peak of spectrum MS n with M-90 and M-120 fragments indicating for C-glycosides cleavage [14].…”
Section: Identification Of Flavonoidmentioning
confidence: 99%
“…Metabolite profiling is one of the strategies in metabolomics analysis that has been widely used to describe secondary metabolite profiles without going through lengthy processes of metabolite isolation [14]. This approach has been applied to F.deltoidea growing in Malaysia, and several compounds of flavonoid and proanthocyanidin class were identified [12]. Metabolite profiling also has been performed on other ficus species namely F. lyrata, and several compounds of flavonoid, phenolic acid, fatty acid, and sphingolipid were identified tentatively [14].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The plant has been reported as traditional medicine to prevent and cure diseases such as diarrhea, sores lung watery, diabetes, high blood pressure, weak heart, cardiovascular and cure skin diseases [6]. Research showed that the extracts of F. deltoidea have effects as antioxidant [7,8], antidiabetic [7,9], anti-inflammatory [10,11], antinociceptive [12], antibacterial [13][14][15], anti melanogenic [16], antiherpes simplex virus type 1 (HSV-1), antiproliferation in 3T3-L1 adipocytes [17,18] and antiangiogenic effect [19] to name a few. In our previous research, the result revealed that extracts of F. deltoidea leaves inhibited the growth of breast tumor in mice and inhibit enzyme tyrosine kinase activity [20].…”
Section: Introductionmentioning
confidence: 99%